(untitled) (Pandecta Research Law Journal, 2026)
This article examines the dissonance between the normative position of the precautionary principle in Indonesian environmental law and the practice of governance in extractive mining permits following the enactment of the Omnibus Law on Job Creation. Using a normative juridical approach supported by case studies in three locations – coal mining and forestry in Wadas Village, Kutai Kartanegara Regency, and Boven Digoel – the article shows that the shift in the licensing regime from a precaution-based approach to a risk-based licensing approach has weakened the legal instruments that should prevent environmental damage early on, with direct implications for the failure to achieve the 13th Sustainable Development Goal (Climate Action). Unlike existing literature, which generally frames this issue as an implementation failure or misuse of administrative discretion, this article argues that the dissonance is built-in in the architecture of risk-based licensing law itself. By combining Lawrence Friedman’s Legal System Theory and Mahfud MD’s Legal Politics Theory, this article argues that the weakening of the precautionary principle is a product of political configurations that deliberately prioritize the acceleration of extractive investment over the prevention of ecological and climate risks. The article concludes with a proposal for a normative reformulation so that the precautionary principle can function as a genuinely precautionary and accountable legal instrument for national climate mitigation targets